The relationship of empathy and altruism with students' moral judgment. - Lausa, Sarah D.
This research would like to know if there is a relationship between empathy and students' moral judgment, and between altruism and students' moral judgment. This also aimed to know the students' concept of morality. Forty-five of the fourth year high school students of Filamer Christian College, Roxas City participated in the study. Results indicated that no relationship exists between empathy and students' moral judgment. Likewise, no relationship was found between altruism and students' moral judgment. Findings also showed that "personhood", as the shared humanity and kapwa psychology of the Filipino was the concept associated with morality.